THE RELATIONSHIP BETWEEN PRINCIPAL LEADERSHIP STYLES AND TEACHER JOB SATISFACTION IN A PUBLIC SCHOOL IN ALMATY, KAZAKHSTAN - Jumabekova, Kassiyet (Nazarbayev University Graduate School of Education, 2025)
While international research has examined how different leadership practices affect teacher motivation and retention, empirical evidence within the Kazakhstani context remains limited. This study explores the relationship between principal leadership styles and teacher job satisfaction in a public school in Almaty, Kazakhstan. Drawing on Bass’s (1985) Transformational and Transactional Leadership Theory, along with alternative frameworks such as authoritarian, democratic, distributed, ethical, people-oriented, and task-oriented leadership, the study uses a qualitative case study approach. Data were collected through semi-structured interviews with one school principal and five teachers. Thematic analysis revealed that both the principal and teachers view leadership as a central factor influencing job satisfaction. The principal associated satisfaction with fairness, trust, creativity, and intrinsic motivation, while teachers emphasised recognition, professional growth, collegiality, and emotional support. Transformational leadership behaviours, such as idealised influence, intellectual stimulation, and individualised consideration, were particularly impactful, although transactional elements were also noted, with mixed responses. Distributed and ethical leadership practices were generally viewed positively, though some participants noted instances of pressure or limited emotional support. The findings suggest that a balanced and context-sensitive leadership approach fosters a more supportive school environment and enhances teacher satisfaction. The thesis concludes by offering practical implications for educational practice, school leadership, and policy development in Kazakhstan’s public-school context, and suggests avenues for further research.
Keywords: principal leadership styles; teacher job satisfaction; transformational leadership; transactional leadership; Type of access: Open